Do Clinical Outcomes and Sagittal Parameters Differ Between Diabetics and Nondiabetics for Degenerative Spondylolisthesis Undergoing Lumbar Fusion?. Issue 3 (May 2020) - Khan, Jannat M.; Michalski, Joseph; Basques, Bryce A.; Louie, Philip K.; Chen, Oscar; Hayani, Zayd; Kalish, Chaim; Elboghdady, Islam; Colman, Matthew; An, Howard
Study Design: Retrospective cohort study. Objective: To assess the effect of diabetes mellitus (DM) on clinical and radiographic outcomes in patient with degenerative spondylolisthesis undergoing posterior lumbar spinal fusion. Methods: Analysis of patients who underwent open posterior lumbar spinal fusion from 2011 to 2018. Patients being medically treated for DM were identified and separated from nondiabetic patients. Visual analogue scale Back/Leg pain and Oswestry Disability Index (ODI) were collected, and achievement of minimal clinically important difference was evaluated. Lumbar lordosis (LL), pelvic tilt (PT), pelvic incidence (PI), and PI-LL difference were measured on radiographs. Rates of postoperative complications were also collected. Results: A total of 850 patients were included; 78 (9.20%) diabetic patients and 772 (90.80%) nondiabetic patients. Final PI-LL difference was significantly larger ( P = .032) for patients with diabetes compared to no diabetes, but there were no other significant differences between radiographic measurements, operative time, or postoperative length of stay. There were no differences in clinical outcomes between the 2 groups. Diabetic patients were found to have a higher rate of discharge to a facility following surgery ( P = .018). No differences were observed in reoperation or postoperative complication. Conclusions: While diabetic patients had more associated comorbidities compared with nondiabetic patients, they had similar patient-reported and radiographic outcomes. Similarly, there are no differences in rates of reoperation or postoperative complications. This study indicates that diabetic patients who have undergone thorough preoperative screening of related comorbidities and appropriate selection should be considered for lumbar spinal fusion.